Causes of slow progress of political economy - Haughton, Samuel (Statistical and Social Inquiry Society of Ireland, 1879)
Political Economy has not of late made progress in public estimation, nor can it be placed in rank, by its most ardent admirers, as a science of which the laws?it may almost be said any one law?are undoubted or capable of positive proof. This state of opinion is partly due to the over-estimate of many writers and advocates, who assumed for this science a position of eminence or control over human affairs, which control is not granted by man, without much contest and directing management, to any of the exact sciences, however clear or forcible may be their laws. These writers asserted that this science of mere wealth was to be the master, not the servant, of man?that, wealth, was to be the perfection of human attainments, and that other human feelings, social, political, artistic, etc., were to be guided and controlled by that one master desire of civilized society!
Read before the Society, 18 February 1879
Keywords: Political economy; Economic science; International economics; Economic laws; 314.15